Printability and quality of papers coated with different binders - ÖZCAN, ARİF; ZELZELE, ÖMER BÜNYAMİN (My University, 2022)
Papers are the most commonly used substrates. A printable paper must have certain properties. These properties include surface smoothness, air permeability, surface energy, colour of the paper, opacity, whiteness, light fastness, gloss, and coefficient of elongation under force. In addition, a good printable paper should not allow ink to pass between its two surfaces. After the papers are produced, they are subjected to surface treatments in order to improve the above-mentioned properties and to provide extra specification. Surface treatments include calendering, surface sizing and coating processes. While filling the recesses and protrusions on the surface with the coating process, the paper's affinity for the ink is increased, and the penetration of the ink to the other surface of the paper is prevented. In the coating process basically, a filler is dispersed in a binder. In this study, it is aimed to obtain the highest quality and most printable paper by changing the type of binder used in the coating. In this study, equal amount (5% w/w) titanium dioxide filler was used in all coating formulations. In coating formulations; cationic starch, hydroxy ethyl cellulose and polyvinyl alcohol polymers were used as binders. Binder amounts are adjusted according to optimum viscosity. The obtained coating formulations were coated on the paper surface with a laboratory type coating device. Colour, gloss, surface smoothness, air permeability, surface energy and surface morphology of the coated papers were determined. It was printed with magenta offset printing ink on three different types of paper coated with different binders, using the IGT C1 offset printability test device, under 400 N/m2 pressure printing conditions. Colour and gloss measurements of the prints were made. As a result; It was determined that three different binders improved the printability parameters.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; binder; paper coating; paper quality; printability; printability; paper coating; binder; paper quality